1996
DOI: 10.1183/09031936.96.09030456
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose theophylline modulates T-lymphocyte activation in allergen-challenged asthmatics

Abstract: Theophylline has been shown by several investigators to attenuate the late asthmatic response (LAR) to inhaled allergen, suggesting that it has antiinflammatory or immunomodulatory properties. We have, therefore, undertaken a double-blind, placebo-controlled study to examine the effects of low-dose theophylline on bronchoalveolar lavage (BAL) and blood T-lymphocyte profile and activation in asthmatics following antigen challenge and the development of a LAR.Peripheral blood and BAL samples were obtained from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 37 publications
2
30
2
Order By: Relevance
“…Values are calculated as 100 -(cytokine expression with PHA/PMA and dexamethasone/cytokine expression with PHA/PMA only)6100. the number of CD4+ lymphocytes in bronchoalveolar lavage (BAL) fluid and a corresponding elevation of these cells in peripheral blood [27]. Moreover, the authors in the latter study [27] found that theophylline therapy appeared to be associated with a reduction in the absolute numbers of BAL CD4+ T-cells expressing activation markers but not a decrease in the proportion of these cells. In other words, the drug may have modulated the movement both of activated and nonactivated lung CD4+ Tcells rather than acting directly to inhibit the activated status of CD4+ cells.…”
Section: ±10mentioning
confidence: 81%
“…Values are calculated as 100 -(cytokine expression with PHA/PMA and dexamethasone/cytokine expression with PHA/PMA only)6100. the number of CD4+ lymphocytes in bronchoalveolar lavage (BAL) fluid and a corresponding elevation of these cells in peripheral blood [27]. Moreover, the authors in the latter study [27] found that theophylline therapy appeared to be associated with a reduction in the absolute numbers of BAL CD4+ T-cells expressing activation markers but not a decrease in the proportion of these cells. In other words, the drug may have modulated the movement both of activated and nonactivated lung CD4+ Tcells rather than acting directly to inhibit the activated status of CD4+ cells.…”
Section: ±10mentioning
confidence: 81%
“…A small study demonstrated a partial inhibition of the LAR but little effect on the induced AHR (87). There are few studies addressing airway inflammation; however, one study showed no inhibition of allergeninduced airway eosinophilia while noting a reduction in activated T cells (88).…”
Section: Bronchodilatorsmentioning
confidence: 99%
“…In man, theophylline inhibits the allergeninduced late asthmatic response (LAR) and associated hyperresponsiveness [5,6]. Six weeks of treatment with theophylline has been shown to reduce the number of activated eosinophils recruited to the airway following allergen challenge, and decrease the numbers of activated CD4+ cells in bronchoalveolar lavage (BAL) fluid postchallenge [7,8]. In another study, withdrawal of theophylline treatment in asthmatic patients was accompanied by a fall in activated CD4+ cells in the peripheral blood and a concomitant increase in T-cells within the bronchial epithelium [9].…”
mentioning
confidence: 99%